KERAGAAN PERTUMBUHAN DAN TINGKAT KELAYAKAN USAHA TANI TIGA VARIETAS BAWANG MERAH : STUDI KASUS DI KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Yulie Oktavia; Yartiwi Yartiwi; Ahmad Damiri (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[PERFORMANCE OF GROWTH AND ANALYSIS OF FARM BUSINESS THREE SHALLOT VARIETIES : CASE STUDY IN SELUPU REJANG REJANG LEBONG REGENCY PROVINSI BENGKULU]. The results of shallots from one region to another in Indonesia are very varied, which is partly due to differences in varieties cultivated. However, high productivity does not necessarily lead to high income. The research aims to compare the productivity and farming of three varieties of shallots, namely Maja Cipanas, Batu Ijo, and Selupu Merah.  This research was conducted in June - July 2018 in Air Duku Village, Selupu Rejang District, Rejang Lebong Regency. Data collected includes agronomic performance (plant height, wet tuber/clump weight, number of tubers/clump, tuber weight, and tuber diameter) and farm economic performance (input, output, and income costs).  The results showed that the wet tuber productivity of the greatest Selupu Merah varieties compared to Batu Ijo and Maja Cipanas, respectively, amounted to 24.47 tons/ha, 22.30 tons/ha, and 14.07 tons/ha. Average plant height, wet tuber weight per clump, weight per tuber, and tuber productivity of Selupu Merah varieties showed the highest results and were significantly different from Batu Ijo and Maja Cipanas. The exciting thing from this research; although Selupu Merah variety shows agronomic superiority, Maja Cipanas variety is more profitable to be cultivated. The value of the RC Ratio of Maja Cipanas variety is 2.81, with a total income of Rp 330,645,000 /ha/planting season. This value is higher than that of Batu Ijo and Selupu Merah varieties, with RC Ratio values of 1.85 and 1.49, respectively, and total income of Rp 379,100,000 and 305,875,000 /ha/planting season. This research shows that although crop productivity is higher, it is not necessarily more economically feasible.